(untitled) (PJDOL, 2023)
Home is the first institution of a child that have significant relationships with students’ overall life. Current study have investigated the relationship of home enviornemnt with secondary school students performances. The focus of the study was to findout the relationship of home interactions, physcial facilities and students academic performances.